La Cachette de karnak : nouvelles perspectives sur les découvertes de Georges Legrain - Coulon, Laurent, 1970- (Biliothque d'etude ;)
The Karnak Cachette, excavated by Georges Legrain between 1903 and 1907, is one of the most fascinating discoveries of Egyptian archaeology. The first reason lies in the very high number of objects found in it (statues, stelae, furniture of various kinds), some of them still unpublished, all of which are documents of major importance for the religious life of Karnak, but also more generally for the history and art of Pharaonic Egypt between the Middle Kingdom and the Ptolemaic period. The second reason is that the raison d'être of this cache and the historical circumstances surrounding its creation remain mysterious. Even if some comparisons can be made with other caches found in Egypt and the Sudan, its magnitude and wealth are exceptional. Building on a research program launched by the Ifao and the Egyptian Ministry of Antiquities to improve our knowledge of the Karnak Cachette and its content, this book comprises twenty-four contributions by international scholars studying objects found in this deposit, analyzing the Cachette itself, or investigating other Egyptian caches from an ideological or archaeological point of view."--Back cover. |u www.ifao.egnet.net/publications/catalogue/978-2-7247-0657-4